Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Asesment Kompetensi Minimum Berdasarkan Teori Kastolan - Novita Anggraini; Dwi Priyo Utomo; Rizal Dian Azmi (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
In studying geometry, it is common for students to make various errors when working on word problems. Although some students understand the example problems, they may be confused and make errors when presented with different questions. This study employed a qualitative descriptive approach to examine the types and causes of errors made by Grade 8 students from a junior high school in Pronojiwo, Indonesia. The study involved 40 students, with six students selected for interviews. Data were collected using descriptions and interviews. The research employed three procedural stages: preparation, implementation, and data analysis. Data analysis involved data reduction, data encoding, and conclusions. The analysis revealed that 23.3% of students made conceptual errors, 27% made procedural errors, and 44.5% made technical errors. The factors contributing to these errors included students' lack of focus on reading the questions, limited understanding of the material, haste in completing the questions, insufficient knowledge of the problems in the questions, and carelessness in checking their answers.